Six-month effects of integrative treatment, therapeutic acupuncture and conventional treatment in alleviating psychological distress in primary care patients - follow up from an open, pragmatic randomized controlled trial - Arvidsdotter, Tina (BioMed Central, 2014)
BACKGROUND: To evaluate and compare 6-month effects of 8 weeks of an integrative treatment (IT), therapeutic acupuncture (TA), and conventional treatment (CT) in reducing symptoms of anxiety, depression and in improving health-related quality of life (HRQL) and sense of coherence (SOC) in psychologically distressed primary care patients. METHODS: Patients who had participated in an open, pragmatic randomized controlled trial were followed up six months after treatment. The study sample consisted of 120 adults (40 per treatment arm) aged 20 to 55 years referred from four different primary health care centres in western Sweden for psychological distress. Assessments were made at baseline after eight weeks and after 24 weeks. Anxiety and depression were evaluated with the Hospital Anxiety and Depression scale (HADS), HRQL with the SF-36 Mental Component Summary scores (MCS) and SOC with the Sense of Coherence-13 questionnaire. RESULTS: No baseline differences were found between groups on any outcome variable. At 24 weeks, IT and TA had significantly better values than CT on all variables. All three groups showed significant improvements from baseline on all variables, except HAD depression in CT; however, improvements were significantly greater in IT and TA than in CT. IT and TA did not differ on any outcome variable. Effect sizes were large in IT and TA for all variables and small or moderate in CT. Improvements on all variables seen after 8-weeks of IT and TA remained stable at 24 weeks and the CT group improved on HAD anxiety. CONCLUSIONS: IT and TA seem to be more beneficial than CT in reducing anxiety, depression, and in improving quality of life and sense of coherence after 24 weeks of follow up in patients with psychological distress. More research is needed to confirm these results. TRIAL REGISTRATION: ISRCTN trial number NCT01631500.